Investigating the Phenomenon of Directed Motivational Current (DMC) in EFL Learners: A Case Study on How DMC Works for ESP Learners - Abbas, Aswin (Proceedings of International Conference on Islamic Civilization and Humanities, 2025)
Directed Motivational Current (DMC), or DMCs, is a new theory in the field of applied linguistics introduced by Dornyei and his colleagues (2015). Although research on DMC in second language acquisition (L2) has advanced recently, systematic analysis of EFL learners remains insufficient. In this context, through an activity-theoretic lens and the novelty of this theory, this study examined how EFL learners experience the key aspects of DMC. The three students identified as having DMC took part in this research. Data were gathered through observations and semi-structured interviews. The results revealed that when EFL learners experience DMC, they engage with all the core elements of DMC, including goals and vision, triggering factors, salient facilitative structures, and positivity emotionality. Further, personalized learning experiences, supportive learning environments, and ongoing self-reflection were crucial for maintaining motivation and achieving language proficiency. Students who actively monitor their progress, celebrate their achievements, and manage their time and resources effectively demonstrate a greater capacity for sustained engagement and successful language acquisition. These results emphasise that while everyone is motivated, not all experience DMC. EFL learners illustrate this, indicating a crucial opportunity to develop and explore how DMC affects English learning.